2019
DOI: 10.20546/ijcmas.2019.807.172
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Onion Production in Sikar District of Rajasthan, India

Abstract: India ranks first by area (12.71 lakh hectare) in onion and second in production (215.63 lakh tonnes) next to China, but productivity is 16.1 tonnes hectare which is low as compared to Netherland, USA, China and the other countries. During 2016-17 India exported 34.93 lakh tonnes of onion (Anonymous, 2017). The reason for low productivity may be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…2) from 2000-01 to 2015-16, Overall CAGR in area, production and productivity of Onion in Tamil Nadu were found to be 1.27 per cent, 2.22 per cent and 1.01 per cent, respectively. Similarly, Singh and Choudhary [4], Kallo and Singh [5], Malik et al, [6], Swati Sharma., [1] in their studies, they also observed increasing trends in area, production and productivity of onion in various parts of the country including vegetables.…”
Section: Compound Annual Growth Ratementioning
confidence: 89%
See 2 more Smart Citations
“…2) from 2000-01 to 2015-16, Overall CAGR in area, production and productivity of Onion in Tamil Nadu were found to be 1.27 per cent, 2.22 per cent and 1.01 per cent, respectively. Similarly, Singh and Choudhary [4], Kallo and Singh [5], Malik et al, [6], Swati Sharma., [1] in their studies, they also observed increasing trends in area, production and productivity of onion in various parts of the country including vegetables.…”
Section: Compound Annual Growth Ratementioning
confidence: 89%
“…Similarly, Singh and Choudhary [4], Kallo and Singh [5], Malik et al, [6] Swati Sharma., [1] in their studies, they also observed increasing trends in area, production and productivity of onion in various parts of the country including vegetables.…”
Section: Percentage Change In Area Production and Productivitymentioning
confidence: 89%
See 1 more Smart Citation
“…Storage is one of the most important aspects of the post-harvest handling of onions. Proper storage conditions extend the period of availability of fresh onions by arresting metabolic breakdown and decay (Sharma & Shukla, 2016). Proper preharvest and post-harvest conditions are also important factors for the stability of onion bulbs as they may also affect their marketability and quality (Petropoulos, Ntatsi, & Ferreira, 2017).…”
Section: Processingmentioning
confidence: 99%